The Business Case for Gender-Responsive Climate-Smart Mining - International Finance Corporation (Washington, DC, 2022)
Transitioning to a low-carbon economy is critical to the sustainability of the planet. A recent World Bank report found that increasing demand for clean energy technologies can increase demand for minerals such as graphite, lithium, and cobalt by nearly 500 percent by 2050. Even though the authors expect recycling rates to go up in the future, mining will still be required to supply critical minerals: the shift to a low-carbon future will be mineral-intensive, and mining will remain a critical industry. It is in this context that the World Bank Group established the climate-smart mining initiative (CSM), which is sustained by a partnership between industry and country governments. The initiative supports the sustainable extraction, processing, and recycling of the minerals and metals that are needed for low-carbon technologies. The concept is built upon four pillars: (i) climate mitigation; (ii) climate adaptation; (iii) reducing material impacts; and (iv) creating market opportunities.